Coagulation Therapy and Thrombosis - Hoyle, Brian (MD Conference Express, 2014)
More cancer patient-specific data are needed to guide prevention and treatment of venous thromboembolism in patients with cancer. Longer-term treatment decision factors include bleeding risk and sex. Catheter removal in the event of thrombosis should be considered carefully. Direct oral anticoagulants are discouraged.